Stochastic Frontier Production Function and Efficiency Status of Poultry Layer Farms in Malaysia - Elpawati; Gabdo, Bashir Hamman; Ismail, Mohd Mansor; Abdurofi , Ilmas (International Journal of Poultry Science, 2018)
Background and Objective: The high cost of production, in particular feed costs in poultry production, is alarming. This study was conducted to identify patterns of production and sources of waste in resource utilization. Materials and Methods: Stochastic frontier production function (SFPF) model was used to measure the output elasticities and investigate the inefficiency effect in Malaysia’s poultry layer farms. Results: Our findings reveal output elasticities of 1.461 (p<0.01), 0.275 (p<0.10), 0.048 and -0.130 (p<0.05), for day-old chicks (DOCs), labour, operation costs and feeds, respectively; DOCs is the only elastic input and the most important. The results show the presence of approximately 12% noise in poultry egg production. The study revealed overutilization of inputs (input slacks), with feeds (89.46%), labour (39.74%), operation costs (1.40%) and DOCs (1.34%) ranked as the first, second, third and fourth most over utilized inputs, respectively. Conclusion: To reduce inefficiency in poultry layer production, inputs should be reduced by the proportion of input slacks evaluated and farmers should strive to operate closed systems of layer production and update their knowledge and skills with the latest production and managerial techniques for improved efficiency and least-cost production. Finally, we recommend that farmers produce at a scale commensurate with the availability of inputs to achieve increases in scale efficiency.